2016
DOI: 10.5223/pghn.2016.19.4.229
|View full text |Cite
|
Sign up to set email alerts
|

Early Infant Feeding Practices May Influence the Onset of Symptomatic Celiac Disease

Abstract: PurposeTo study whether breastfeeding and breastfeeding status during gluten introduction influences the age at diagnosis of celiac disease (CD). In addition to study, whether the timing of gluten introduction influences the age at diagnosis of CD.MethodsIt was a hospital based observational study. Total 198 patients diagnosed with CD as per modified European Society of Pediatric Gastroenterology, Hepatology and Nutrition (2012) criteria, aged between 6 months to 6 years were included. Detail history taken wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Therefore, a recent study performed by Vajpayee et al on pediatric patients found that breastfeeding at the time of gluten introduction to an infant's diet and beyond this moment will delay the age of CD diagnosis. [19] Similarly, a meta-analysis conducted by Akobeng et al also stated that infants still breastfed at the moment of gluten introduction to the diet presented a 52% lower risk of developing CD. [20] Nevertheless, prospective studies failed in proving the protective role of breastfeeding against the development of CD in small children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a recent study performed by Vajpayee et al on pediatric patients found that breastfeeding at the time of gluten introduction to an infant's diet and beyond this moment will delay the age of CD diagnosis. [19] Similarly, a meta-analysis conducted by Akobeng et al also stated that infants still breastfed at the moment of gluten introduction to the diet presented a 52% lower risk of developing CD. [20] Nevertheless, prospective studies failed in proving the protective role of breastfeeding against the development of CD in small children.…”
Section: Discussionmentioning
confidence: 99%
“…Further, why should some atopic diseases such as asthma ( 12 ), atopic dermatitis ( 13 ), and celiac disease ( 6 ), be associated with altered small bowel permeability but not EoE? Th ey are all at least partly antigen driven, and may share similar microbiome risk factors such as lack of breast feeding, early exposure to antibiotics and higher likelihood of Cesarian section (14)(15)(16)(17). I would speculate these groups of diseases are more likely to have a similar core pathophysiology.…”
mentioning
confidence: 99%